Asymmetric spin crossover behaviour and evidence of light-induced excited spin state trapping in a dinuclear iron(II) helicate - SCHMITT, WOLFGANG (My University, 2009)
Reported herein are the synthesis, structural and magnetic characterisation of a dinuclear FeII triple helicate that displays an unprecedented reversible asymmetric high spin to low spin crossover characterised by a thermal hysteresis: indeed the high spin state can be recovered by white light irradiation at 10 K.
PUBLISHED
Keywords: FeII triple helicate